2020
DOI: 10.3390/ijerph17113754
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Gender-Based Violence and Sexual Harassment in University Students: Analysis of the Information Sources and Risk within a Relationship

Abstract: In a truly democratic society, there should be no place for any kind of discrimination or violence. Among the basic tools for eradicating discrimination and violence against women, education has a crucial role to play. Education about gender should be considered at all levels, in all year groups and across the curriculum, so as to improve education about this subject. Although these matters are increasingly addressed, at university level, including at postgraduate level, they are often forgotten. The purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
(32 reference statements)
4
6
0
1
Order By: Relevance
“…This report further documented that over 60% of the respondents could clearly indicate the de nition of gender-based violence. This is in tandem with ndings in a similar study whose respondents showed a satisfactory knowledge of gender-based violence with over 69% scoring above average as they have could clearly describe gender-based violence 10,11 . This study further showed that 72.9% young adults could identify the various forms of gender-based violence with 20.3% indicating that lecturers and teachers are the commonest perpetrators of gender-based violence.…”
Section: Knowledge Of Gender-based Violence Among Young Adultssupporting
confidence: 83%
See 1 more Smart Citation
“…This report further documented that over 60% of the respondents could clearly indicate the de nition of gender-based violence. This is in tandem with ndings in a similar study whose respondents showed a satisfactory knowledge of gender-based violence with over 69% scoring above average as they have could clearly describe gender-based violence 10,11 . This study further showed that 72.9% young adults could identify the various forms of gender-based violence with 20.3% indicating that lecturers and teachers are the commonest perpetrators of gender-based violence.…”
Section: Knowledge Of Gender-based Violence Among Young Adultssupporting
confidence: 83%
“…Finally, this study showed that generally, respondents had a moderate knowledge of gender-based violence with an average of 12.02 out of 18 points. 15 . This study also revealed that 18.2% of victims did not report to anyone about when they experienced GBV while 19.9% indicated that if they were to experience gender-based violence, they would keep it to themselves.…”
Section: Knowledge Of Gender-based Violence Among Young Adultsmentioning
confidence: 99%
“…In another school-based study in Ethiopia, sexual violence and physical violence were 37.2% and 56.3% respectively [15]. In addition, other authors have reported harassment [16,17]. A systematic review in sub-Saharan Africa also reveals other forms including emotional violence (29.40%) [18].…”
Section: Discussionmentioning
confidence: 94%
“…Gender-based violence seriously impacts the immediate physical and psychological health of survivors and contributes to a greater risk of future health problems. Osuna-Rodrigues et al agreed that the impacts of gender-based violence lasts long even after the incidence and can affect the survivor's self-esteem and quality of life, while contributing to exposing him or her to further abuse [10].…”
Section: Health Outcomes Associated With Gender-based Violencementioning
confidence: 99%